TERMINAL BARANG SEBAGAI SISTEM PENDATAAN BARANG DI KOPERASI SMP NEGERI 23 SEMARANG BERBASIS WEB - Cholil, Saifur Rohman; Putri, Amelia Widya Octa Kuncoro (Jurnal Pengembangan Rekayasa dan Teknologi, 2019)
Computerized systems are now commonly used including school cooperatives, but not all school cooperatives maximize the use of computer systems. Administrative activities and data collection are still done manually, by recording all activities into the book according to the activities carried out. The development of information technology at this time, efficiency can easily be applied using the implementation of information technology. The expectation of this information technology implementation is that cooperative data management is not done manually. Making a cooperative data collection system will simplify, accelerate cooperative staff in inputting goods data, search goods and sales and purchase transactions. So that hope can be achieved with the help of cooperative data collection system. The method used in building a cooperative data collection system is the prototyping method, where later this system can be developed again. Cooperative goods data collection system is built with the PHP programming language and database used is MySQL, while in system depiction, in general, using the Unified Modeling Language. The facilities contained in this system are the process of purchasing transactions, sales transaction processes, managing goods, managing suppliers, printing sales reports, printing purchase reports, printing profit reports and managing users. Besides aiming to facilitate cooperative staff in managing cooperative goods data, it also provides added value for the administration of Semarang State Junior High School 23 in the implementation of the paperless office